Octopus‐Inspired Adhesives with Switchable Attachment to Challenging Underwater Surfaces - Chanhong Lee; Austin C. Via; Aldo Heredia; Daniel A. Adjei; Michael D. Bartlett (Advanced Science)
Abstract Adhesives that excel in wet or underwater environments are critical for applications ranging from healthcare and underwater robotics to infrastructure repair. However, achieving strong attachment and controlled release on difficult substrates, such as those that are curved, rough, or located in diverse fluid environments, remains a major challenge. Here, an octopus‐inspired adhesive with strong attachment and rapid release in challenging underwater environments is presented. Inspired by the octopus's infundibulum structure, a compliant, curved stalk, and an active deformable membrane for multi‐surface adhesion are utilized. The stalk's curved shape enhances conformal contact on large‐scale curvatures and increases contact stress for adaptability to small‐scale roughness. These synergistic mechanisms improve contact across multiple length scales, resulting in switching ratios of over 1000 within ≈30 ms with consistent attachment strength of over 60 kPa on diverse surfaces and conditions. These adhesives are demonstrated through the robust attachment and precise manipulation of rough underwater objects.